FRI0152 Decreased Employment, Work Productivity, and Presenteeism in Patients with Ankylosing Spondylitis is Associated with Increased Disease Activity as Measured by Basdai. (10th June 2014) - Maksymowych, W.P.; Boonen, A.; Marzo-Ortega, H.; Magrey, M.; Joshi, A.; Halpern, M.; Renaud, J.; Mittal, M.; Bao, C.
Abstract : Background: Ankylosing spondylitis (AS) results in substantial burden to patients. The Bath AS Disease Activity Index (BASDAI) has been used as a primary endpoint in clinical trials involving patients with AS; however the relationship between BASDAI and patient-reported work productivity is not well understood. Objectives: To evaluate the relationship between disease activity and patient-reported measures of work productivity. Methods: Data were drawn from a prospective multicenter Patient Reported Outcomes Survey of Employment in Patients with AS (PROSE AS). Patients ≥18 years completed a survey that included demographics, comorbidities, employment, work productivity measures (Work Productivity and Activity Impairment [WPAI], Work Limitations Questionnaire [WLQ-25], Workplace Activity Limitation Scale [WALS]), and assessment of disease activity (BASDAI). Multivariable logistic regression analyses, adjusting for potential confounding factors were performed to evaluate the relationship between BASDAI (low (<4) vs. moderate (≥4 to <6) and high (≥6)) and patient-reported work measures at baseline. Results: There were 555 patients, mean age 46.71 years; 71% were male and 93% were Caucasian. The mean BASDAI for the entire group was 4.15, suggesting sub optimal disease control. Most patients (n=376; 67.7%) were employed. Of the employed patients, 54.8% (n=206) had low BASDAI, 25.0% (n=94) moderate, and 20.2% (n=76) high. Of not employed (n=177), 34.5% (n=61) had a low BASDAI score, 29.4% (n=52) moderate, and 36.2% (n=64) high. The adjusted odds of not being employed were 2.56 times greater in patients with high BASDAI than those with low BASDAI (table). When compared to patients with low BASDAI, the odds of absenteeism (WPAI) were 2.66 times greater in participants with high BASDAI; presenteeism (WPAI) was 2.90 and 6.96 times more likely for participants with moderate and high BASDAI, respectively. Results were consistent across other work productivity measures (WLQ-25 and WALS). Conclusions: Among participants in PROSE AS, increased disease activity as measured by BASDAI was significantly associated with loss of patient-reported work productivity. Disclosure of Interest: W. Maksymowych Grant/research support: AbbVie, Consultant for: AbbVie, Speakers bureau: AbbVie, A. Boonen Grant/research support: Amgen, AbbVie, Merck, Speakers bureau: UCB, Pfizer, H. Marzo-Ortega Grant/research support: AbbVie, MSD, UCB, Pfizer, Janssen, Consultant for: AbbVie, MSD, UCB, Pfizer, Janssen, Speakers bureau: AbbVie, MSD, UCB, Pfizer, Janssen, M. Magrey Consultant for: AbbVie, Employee of: MetroHealth, A. Joshi Shareholder of: AbbVie, Employee of: AbbVie, M. Halpern Grant/research support: AbbVie, J. Renaud Grant/research support: AbbVie, M. Mittal Shareholder of: AbbVie, Employee of: AbbVie, C. Bao Shareholder of: AbbVie, Employee of: AbbVie DOI: 10.1136/annrheumdis-2014-eular.2149